2004
DOI: 10.1002/hup.630
|View full text |Cite
|
Sign up to set email alerts
|

The effects of methadone and its role in fatalities

Abstract: Methadone is a synthetic opioid, used both as an analgesic in severe pain relief and now mainly in the treatment of opiate dependence. Such use of the drug has increased as its advantages have become widely recognized. There are undesirable outcomes from its greater use, including a substantial market in diverted methadone and a high number of deaths where the drug has been implicated. It is important to understand how and why methadone causes death so that such fatalities can be minimized, and to disseminate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0
15

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(112 citation statements)
references
References 97 publications
5
92
0
15
Order By: Relevance
“…Furthermore, methadone in the initial phase of methadone replacement therapy has been shown to be slowlymetabolized (Corkery et al, 2004). More specifically, according to Wolff et al (2000) the median elimination half-life of methadone has been found to be diminished more than 60% when the addict has reached a steadystate methadone level.…”
Section: Limitations Of Existing Resting-state Literaturementioning
confidence: 99%
“…Furthermore, methadone in the initial phase of methadone replacement therapy has been shown to be slowlymetabolized (Corkery et al, 2004). More specifically, according to Wolff et al (2000) the median elimination half-life of methadone has been found to be diminished more than 60% when the addict has reached a steadystate methadone level.…”
Section: Limitations Of Existing Resting-state Literaturementioning
confidence: 99%
“…It takes 2-4 hours to achieve peak plasma levels. 15 Methadone is metabolized primarily in the liver into inactive metabolites by the P450, CYP 3A4 enzymes that are also used by several QTc prolonging medications. 16,17 Methadone is a weak inhibitor of the 3A4 system and a minor weak substrate of 2C89, 2C19 and 2D6.…”
Section: Pharmacologymentioning
confidence: 99%
“…Thus, individuals prescribed methadone for pain generally experience relief for 4-8 hours, but methadone remains pharmacologically active for much longer periods, potentially leading to toxicity. 15 Although individuals receiving MMT typically take methadone only once daily, 8 its pharmacologic properties may interact with relatively rapid titration regimens to cause increases in serum levels in opioid dependent patients.…”
Section: Respiratory Depressionmentioning
confidence: 99%
See 2 more Smart Citations